2002
DOI: 10.1099/00221287-148-9-2869
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of the ferric hydroxamate uptake (fhu) operon in Actinobacillus pleuropneumoniae The GenBank accession number for the sequence of the fhuCDBA operon of Actinobacillus pleuropneumoniae serotype 1 reference strain 4074 described in this study is AF351135.

Abstract: The bacterium Actinobacillus pleuropneumoniae, a swine pathogen, utilizes ferrichrome as an iron source. This study details the molecular cloning and sequencing of the genes involved in the uptake of this hydroxamate siderophore. Four ferric hydroxamate uptake (fhu) genes, fhuC, fhuD, fhuB and fhuA, were identified in a single operon, and these were found to encode proteins homologous to proteins of the fhu systems of several bacteria, including Escherichia coli. The fhuA gene encodes the 77 kDa outer-membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 56 publications
(41 reference statements)
1
20
1
Order By: Relevance
“…The presence of fhuCDBA genes clearly supports the concept that H. parasuis strains may count for all the necessary Fhu proteins for capturing iron from siderophores. However, these results disagree with others reported recently in the literature [20] The relative position of the four genes in the H. parasuis Fhu region was identical to that of A. pleuropneumoniae [19], in which the fhuC gene is followed by the fhuD, fhuB and fhuA genes, whereas in E. coli or S. Typhimurium the fhuA is followed by fhuC, fhuD and fhuB [11,18]. The different relative position of the four genes in H. parasuis and A. pleuropneumoniae, as compared to E. coli and S. Typhimurium fhu genes, might account for the differences in the regulation of the FhuA protein expression observed in the former species.…”
Section: Discussioncontrasting
confidence: 85%
“…The presence of fhuCDBA genes clearly supports the concept that H. parasuis strains may count for all the necessary Fhu proteins for capturing iron from siderophores. However, these results disagree with others reported recently in the literature [20] The relative position of the four genes in the H. parasuis Fhu region was identical to that of A. pleuropneumoniae [19], in which the fhuC gene is followed by the fhuD, fhuB and fhuA genes, whereas in E. coli or S. Typhimurium the fhuA is followed by fhuC, fhuD and fhuB [11,18]. The different relative position of the four genes in H. parasuis and A. pleuropneumoniae, as compared to E. coli and S. Typhimurium fhu genes, might account for the differences in the regulation of the FhuA protein expression observed in the former species.…”
Section: Discussioncontrasting
confidence: 85%
“…salmonis is a Gram-negative bacterium, the expressed genes also encoded proteins of the TonB system, which is a sophisticated mechanism that supplies the required energy for ferri-siderophores uptake. The TonB system includes an integral membrane protein (ExbB), a membrane-anchored periplasmatic protein (ExbD) and the TonB protein [78,79]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies of A. pleuropneumoniae expression by polyacrylamide gel electrophoresis and immunoblotting have demonstrated that proteins encoded by tpbA and exbB are expressed only under iron-limiting growth conditions (5,25). Another A. pleuropneumoniae iron transport system, via ferrichrome, was represented in the analysis by a gene coding for ferric hydroxamate uptake protein (fhuD), which is part of the fhuCDBA operon (14). Previous results indicated that the regulation of fhuA appears to be independent of the iron supply (15).…”
mentioning
confidence: 99%